Response of Entres Age and Clone to Growth of Rubber Seedling (Hevea brasiliensis Muell. Arg) - Railia Karneta; M. Manisah (Universitas Sembilanbelas November Kolaka, 2020)
Effort to increase rubber plant production should be done, especially rejuvenation for old rubber plant which in turn require high numbers of seedling within short time period. One of the method to provide rubber plant seedlings within short time period is through grafting technique which combine plant having strong rootas base stem and high production plant as upper stem (entres). The objective of this research was to study response of entres age and clone to growth of rubber seedling (Hevea brasiliensis Muell, Arg.) produced from green and brown grafting. This study was conducted from February 2019 to Februari 2020. This study used Factorial Randomized Block Design with entres age as the first factor consisting of 3, 6, 9, 12 and 15 months as well as clone as the second factor consisting of PB 260 and BPM 24. Data was analyzed by using analysis of variance and followed bywith Honestly Significant Different (HSD) test and regression analysis. The study results showed that the best treatment was entres having 9 months of age as indicated by grafting success, the speed of stum out, stumlength, stumdry weight, root length androot dry weight which had the highest values than that of other treatments. Clone of PB 260 was the best entres that was very compatible with base stem of GT1 clone than that of BPM 24 clone because it gave the highest yield in term of all observed parametes. The interaction between 9 month entres age and PB 260 clone was the best treatment